2011
DOI: 10.1177/193229681100500535
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Pilot Internet-Based Weight Management Program (H.E.A.L.T.H.) and Longitudinal Physical Fitness Data in Army Reserve Soldiers

Abstract: Background: The primary aims of this article are to describe the utilization of an Internet-based weight management Web site [Healthy Eating, Activity, and Lifestyle Training Headquarters (H.E.A.L.T.H.)] over a 12–27 month period and to describe concurrent weight and fitness changes in Army Reserve soldiers. Methods: The H.E.A.L.T.H. Web site was marketed to Army Reserve soldiers via a Web site promotion program for 27 months (phase I) and its continued usage was observed over a subsequent 12-month period (pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…For Army soldiers, weight loss (≥5% of weight) was associated with usage of the program website . All Reserve website‐users, however, gained weight during the study period .…”
Section: Healthcare In the Militarymentioning
confidence: 95%
“…For Army soldiers, weight loss (≥5% of weight) was associated with usage of the program website . All Reserve website‐users, however, gained weight during the study period .…”
Section: Healthcare In the Militarymentioning
confidence: 95%
“…Indeed, findings from other studies (e.g., see [19, 20]) suggest that patients that are referred to PA by GPs are more likely to be active than those who are referred by a visiting specialist. Interestingly, studies have also suggested that the effectiveness of interventions aimed at promoting PA, in both healthy adults [21, 22] and T2D patients [23, 24], may be enhanced when traditional methods are supported by the use of web-based applications (WBA).…”
Section: Introductionmentioning
confidence: 99%
“…Níveis elevados de aptidão física entre militares são relevantes para a segurança pública e da nação e, em âmbito nacional, no primeiro ano de ingresso, recrutas passam por treinamento intenso para aprimorar suas capacidades físicas e possuírem excelência militar (ROBERT et al, 2011). Porém, internacionalmente, observa-se que a aptidão física dos soldados, após doze meses de serviço militar, diminui significativamente quando comparada à do ano de conscrito (DREGVAL;VAIČAITIENĖ, 2006).…”
unclassified